Analysis Operational Efficiency Strategy and Improvement of Hotel Housekeeping Communication System - Widiastini, Ni Made Ary; Santiara, I Made; Rahmawati, Putu Indah (Jurnal Manajemen Pelayanan Hotel, 2024)
This study aims to analyze the internal communication needs that affect Housekeeping operations in a hotel. Pareto analysis is used in this study to find significant causes. Furthermore, Fishbone analysis (cause and effect) is used to systematically visualize and understand cause-and-effect relationships, which helps in identifying critical areas that need improvement. The root problems in the Housekeeping Department were identified, namely (1) Skill and knowledge gaps; (2) Lack of adequate leadership; (3) Generational differences and organizational culture; (4) Lack of advanced training causes employees not to get increased skills, as well as understand the roles and duties of other departments (cross-training) which has an impact on cross-departmental communication. By identifying the root cause analysis, solution steps can be developed, such as increasing the frequency of communication training, implementing cross-training between departments, and preparing effective leadership training for employees. This can be done by compiling a timeline for solutions to handling communication problems. It is recommended that improvements be made to the communication system in the housekeeping department including improving communication technology, developing clearer Standard Operating Procedures (SOPs), providing better communication skills training for staff, and improving cross-departmental coordination.